Measurement of the serum level of Elabela for the early detection of acute kidney injury in hospitalized Iraqi COVID-19 patients - Gadhi, Maha H.; S. Saleh, Eman (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is caused coronavirus disease 2019 (COVID-19) affecting people worldwide. The angiotensin converting enzyme2 (ACE2) represents a receptor of SARS-CoV-2 on the infected host cell. Apelin or its receptor agonists suppress the production of angiotensin-converting enzyme (ACE) and angiotensin II (Ang-II) and is characterized by a protective effect against SARS-CoV-2. Objective: The study aims to assess the serum level of Elabela biomarker as an early detector for Acute Kidney Injury (AKI) in patients with COVID-19. Cases and Methods: This is a case-control study which included 45 hospitalized adult patients in multiple centers (public hospitals) receiving COVID-19 cases in Baghdad. These cases had a positive real-time or reverse transcription polymerase chain reaction (RT-PCR) of nasal/oropharyngeal swabs. Excluded from the study were those with a negative PCR and comorbidities and 43 apparently healthy adult subjects as controls. The age range of the cases and controls was (20 to 60) years Result: There are no a statistically significant differences between the two groups in terms of age and gender distribution. Statistically significant differences were found in terms of eGFR, S. Creatinine, D. dimer, NEU×103 /µL, LYM×103 /µL and ELA biomarker. Significant negative correlations were found between Elabela with D. dimer and NEU×103 /µL, and between eGFR with S. creatinine, D. Dimer, and NUT×103 /µL. Conclusion: The Elabela biomarker can be used for the early detection of acute kidney injury in COVID-19 patients.